Porous concrete paving blocks using coarse aggregate - Abdul Halim, Nur Hidayah (Trans Tech Publications, 2014)
The objective of the study is to investigate the potential of using Porous Concrete Paving Blocks (PCPB) as a part of paving surface. Laboratory tests were conducted to compare and examine the effect of particle sizes of coarse aggregate. Two coarse aggregate sizes were selected; passing 8 mm retains 5 mm and passing 10 mm retains 8 mm. The fine aggregate was eliminated from mixes. The water to cement ratio used was 0.35. Compressive strength and skid resistance tests were performed to evaluate the properties of PCPB. The test results indicated that there was a reduction in the strength when coarse aggregate at different size was used. Scanning electron microscopy showed that voids, poor bonding and lack of adhesion at the boundaries of the aggregate with cement paste contributing to the low PCPB strength. However, both PCPB specimens provide 30% to 40% increase in skid resistance compared to Concrete Paving Blocks (CPB).